Solution Properties of Murine Leukemia Virus Gag Protein: Differences from HIV-1 Gag - Datta, Siddhartha A. K. (American Society for Microbiology, 2011)
Immature retrovirus particles are assembled from the multidomain Gag protein. In these particles, the Gag proteins are arranged radially as elongated rods. We have previously characterized the properties of HIV-1 Gag in solution. In the absence of nucleic acid, HIV-1 Gag displays moderately weak interprotein interactions, existing in monomer-dimer equilibrium. Neutron scattering and hydrodynamic studies suggest that the protein is compact, and biochemical studies indicate that the two ends can approach close in three-dimensional space, implying the need for a significant conformational change during assembly. We now describe the properties of the Gag protein of Moloney murine leukemia virus (MLV), a gammaretrovirus. We found that this protein is very different from HIV-1 Gag: it has much weaker protein-protein interaction and is predominantly monomeric in solution. This has allowed us to study the protein by small-angle X-ray scattering and to build a low-resolution molecular envelope for the protein. We found that MLV Gag is extended in solution, with an axial ratio of ∼7, comparable to its dimensions in immature particles. Mutational analysis suggests that runs of prolines in its matrix and p12 domains and the highly charged stretch at the C terminus of its capsid domain all contribute to this extended conformation. These differences between MLV Gag and HIV-1 Gag and their implications for retroviral assembly are discussed.